2017
DOI: 10.1002/anie.201703239
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Controlled Spatiotemporal Oscillations of Colloidal Assemblies

Abstract: We report an autonomous oscillatory micromotor system in which active colloidal particles form clusters, the size of which changes periodically. The system consists of an aqueous suspension of silver orthophosphate microparticles under UV illumination, in the presence of varying concentrations of hydrogen peroxide. The colloid particles first attract each other to form clusters. After a short delay, these clusters abruptly disperse and oscillation begins, alternating between clustering and dispersion of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 53 publications
3
62
0
1
Order By: Relevance
“…[36,146,147] One example is ap eriodical oscillation of cluster size observedi na ne xperiment similart ot hat previously reported. [36,146,147] One example is ap eriodical oscillation of cluster size observedi na ne xperiment similart ot hat previously reported.…”
Section: Rhythmic Behaviorsupporting
confidence: 78%
See 1 more Smart Citation
“…[36,146,147] One example is ap eriodical oscillation of cluster size observedi na ne xperiment similart ot hat previously reported. [36,146,147] One example is ap eriodical oscillation of cluster size observedi na ne xperiment similart ot hat previously reported.…”
Section: Rhythmic Behaviorsupporting
confidence: 78%
“…[36,146,147] One example is ap eriodical oscillation of cluster size observedi na ne xperiment similart ot hat previously reported. [146] This oscillation is considered to be causedb yt wo different chemical reactions:i )decomposition of H 2 O 2 with UV irradiation catalyzed by Ag 3 PO 4 and ii)reaction of H 2 O 2 and OH À ,w hich produces and reduces OH À ,r espectively.F or dispersed particles, the latter reactionb ecomes dominant, resulting in the generation of clusters by attractive electroosmotic effect.O nce the clusters have been formed, the local concentration of OH À increases aroundt he cluster due to the aforementioned chemical reaction, and then the particles are dispersed with electroosmotic flow toward the outside of the cluster. [146] This oscillation is considered to be causedb yt wo different chemical reactions:i )decomposition of H 2 O 2 with UV irradiation catalyzed by Ag 3 PO 4 and ii)reaction of H 2 O 2 and OH À ,w hich produces and reduces OH À ,r espectively.F or dispersed particles, the latter reactionb ecomes dominant, resulting in the generation of clusters by attractive electroosmotic effect.O nce the clusters have been formed, the local concentration of OH À increases aroundt he cluster due to the aforementioned chemical reaction, and then the particles are dispersed with electroosmotic flow toward the outside of the cluster.…”
Section: Rhythmic Behaviorsupporting
confidence: 77%
“…The ability of individuals to maintain their independent behavior, but also be a part of an organized cohesive group, is one of the most interesting characteristics of life. With the discovery and development of synthetic self‐propelled microparticles over the last decade, several systems have been reported that demonstrate complex pattern formation and coordinated motion . Collections of composite polymer‐hematite particles, for example, form living crystals of active particles, which combine and break apart spontaneously in a solution of peroxides and surfactant .…”
Section: Methodsmentioning
confidence: 99%
“…This inspires the design of self‐propelled artificial objects that can respond to external stimuli and reveal collective behavior . Synthetic nano‐ and micromotors reveal self‐propulsion by converting chemical energy into mechanical motion . They interact with their surroundings and realize various scenarios of collective behavior.…”
mentioning
confidence: 99%
“…Recently, light‐driven nano/micromotors stimulated research on their fabrication and characterization . In photochemically‐driven systems, the focus was mainly on various collective behaviors of schooling, oscillation, and assembling . Although fundamentally appealing and relevant for applications to microscale pumping and transport, the opposite effect, e.g., exclusion phenomena between active self‐propelled micromotors and passive beads are much less explored.…”
mentioning
confidence: 99%